The analysis of development of oil-free bearing systems of high-speed compressor and rotary-type power units for mobile operating conditions - N. A. Raykovskiy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article considers an analysis of prospects for the use of oil-free bearings for working conditions in rotary units of autonomous mobile installations. The analysis made it possible to establish the current level of development of oil-free bearing technologies, the existing limitations of their use in units of autonomous mobile installations and urgent problems, the solution of which requires research and further improvement of the designs of bearing units